First report of Rhodnius stali (Hemiptera, Reduviidae, Triatominae) in the State of Acre and in the Brazilian Amazon - Oliveira Meneguetti, Dionatas Ulises de; Souza Castro, Gabriela Vieira de; Lima Ribeiro Castro, Mariane Albuquerque; Souza, Janis Lunier de; Oliveira, Jader de [UNESP]; Rosa, Joao Aristeu da [UNESP]; Aranha Camargo, Luis Marcelo (Soc Brasileira Medicina Tropical, 2016)
Introduction: This paper reports, for the first time, the presence of Rhodnius stali in the state of Acre and in the Brazilian Amazon. Methods: Specimens of R. stali were collected by the Federal University of Acre in Rio Branco. Results: The number of Triatominae species in the State of Acre increased from five to six. This was also the first report of R. stali in the Brazilian Amazon. Conclusions: The occurrence of R. stali is worrisome, since this species has been found naturally infected by Trypanosoma cruzi and there has been evidence of its domiciliation capabilities.
Keywords: Triatominae; Rhodnius stali; Western Amazon